Effect of pre-gestational weight and gestational weight gain in women with gestational diabetes controlled with medication on pregnancy outcomes – is recommended weight gain too liberal?. (3rd April 2019) - Koren, Ronit; Hochman, Yuval; Koren, Shlomit; Ziv-Baran, Tomer; Wiener, Yifat
Abstract: This is a retrospective cohort study of women with GDM treated with glucose-lowering agents that were followed and gave birth between 2005 and 2015 in the Assaf Harofeh medical center, Israel. Classification and regression tree method identified four groups according to adverse outcomes, consisted of 74 women with pre-gestational BMI below 25, 98 women with BMI 25–31, 90 women 31–39 and 18 women above 39. Respectively, median GWG was 12 kg (8–16), 11 kg (8–15), 7.5 kg (3.75–11) and 5 kg (–1.5 to 11.5) ( p  < .001). The risk for composite adverse outcomes was higher in the groups of BMI 25–31 (73.5%) and 31–39 (83.3%) in comparison to BMI <25 (51.4%) and 39 < (55.6%), p  < .001. In women with pre-gestational BMI of <25, GWG of more than the median resulted in odds ratio of 2.75 (1.07–7.08, p  = .036) for adverse pregnancy outcomes compared with participants who gained less than the median. Maternal obesity is related to adverse pregnancy outcomes. Women with GDM with normal pre-gestational BMI who gained weight according to IOM recommendations still experienced adverse outcomes.